1999
DOI: 10.1007/s001980050129
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Osteoporosis in Nursing Home Residents

Abstract: This study describes the prevalence of osteoporosis in a statewide sample of nursing home residents. Composite forearm bone mineral density (BMD) (including the distal radius and the distal ulna) of 1475 residents aged 65 years and older from 34 randomly selected, stratified nursing homes was assessed. BMD was expressed with reference to World Health Organization diagnostic criteria. Trends with age, gender and race were consistent with other populations. However, prevalence estimates were higher than communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 37 publications
1
75
1
1
Order By: Relevance
“…Furthermore, application of hip protectors in nursing homes by staff may be considered an important cointervention, not available in other group residence settings; this issue could be another contributor to clinical heterogeneity of pooled analyses of mixed populations. The nursing home population was of greatest clinical interest, as this population is known to be at extremely high risk for osteoporosis [14][15][16], falls [17], cognitive impairment (leading to falls and hip fracture) [16], and hip fracture [18][19][20].…”
Section: Selection Of Trials For Inclusion and Data Abstractionmentioning
confidence: 99%
“…Furthermore, application of hip protectors in nursing homes by staff may be considered an important cointervention, not available in other group residence settings; this issue could be another contributor to clinical heterogeneity of pooled analyses of mixed populations. The nursing home population was of greatest clinical interest, as this population is known to be at extremely high risk for osteoporosis [14][15][16], falls [17], cognitive impairment (leading to falls and hip fracture) [16], and hip fracture [18][19][20].…”
Section: Selection Of Trials For Inclusion and Data Abstractionmentioning
confidence: 99%
“…According to European studies, 1/3 of women at the age of 60 and 2/3 at the age of 80 suffer from osteoporosis. It has been shown that in people at the age of around 85 residing in old age and nursing homes, the osteoporosis incidence rate ranges from 85.8% to 95% [66,67]. The deficiency of vitamin D active metabolites also contributes to the development of central nervous system diseases, including Parkinson's disease [68,69,70], Alzheimer's disease [70,71], strokes, schizophrenia and depression [72].…”
Section: Przytarczyce Witamina Dmentioning
confidence: 99%
“…Wykazano, że u osób około 85 r.ż. przebywają-cych w domach opieki i pomocy długoterminowej wskaźnik występowania osteoporozy wynosi aż ok. 85,8-95% [66,67]. Deficyt aktywnych metabolitów witaminy D sprzyja również rozwojowi chorób ośrodkowego układu nerwowego (OUN), w tym choroby Parkinsona [68,69,70], choroby Alzheimera [70,71], udarom mózgu, schizofrenii i depresji [72].…”
Section: Przytarczyce Witamina Dunclassified
“…Using data from a previous study of nursing home residents in Maryland [25], we estimated the overall incidence of 5.6 hip fractures per 100 person years of follow-up (or 2.8 hip fractures per hip). In that study, the difference in hip fracture rate between those with and without prior fractures was minimal.…”
Section: Sample Size For Primary Outcomementioning
confidence: 99%